Strategi Guru dalam Memotivasi Siswa pada Penyelesaian Soal Tes Kompetensi Akademik - Ahmad Sultoni; Joko Susilo; Agus Rifai Rahmat; Umartono, Umartono; Umi Muslikhah; Samino, Samino (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the strategies implemented by teachers to increase student motivation when facing and completing Academic Competency Test questions and identify factors that influence the effectiveness of these strategies. The subjects of this study were teachers at Madrasah Aliyah Negeri 2 Magelang, Madrasah Aliyah Negeri 4 Boyolali, Madrasah Tsanawiyah Negeri 4 Klaten, Madrasah Tsanawiyah Negeri 1 Sragen, Madrasah Tsanawiyah Negeri 5 Wonogiri, and Madrasah Tsanawiyah Negeri 5 Klaten. The informants of this study were teachers. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results showed that teachers implemented various strategies, such as providing verbal motivation, constructive feedback, gradual practice, the use of contextual learning methods, and positive reinforcement to increase student self-confidence. The effectiveness of these strategies was influenced by several factors, including students' psychological conditions, learning environment support, teacher-student interactions, the availability of learning resources, and the suitability of the learning approach to students' needs. Overall, this study emphasizes the importance of adaptive and student-centered learning strategies to improve their motivation and ability to solve Academic Competency Test questions.